Climate Effects on Breeding Phenology of Peregrine and Lanner Falcons in the Mediterranean - Sara', Maurizio; Mascara, Rosario; Nardo, Angelo; Zanca, Laura (Ardea, 2022)
We explored the effects of weather on the timing and reproduction of the Mediterranean Peregrine Falcon Falco peregrinus brookei and the Lanner Falcon F. biarmicus feldeggii living on the Mediterranean island of Sicily. We found that the start date of incubation has changed during 1979–2019 and analysed whether incubation timing affected the productivity of both populations and whether the change of incubation date and the quality of breeding sites depended on climatic conditions. Overall spring temperature and rainfall increased on Sicily and the incubation date of the Peregrine and the Lanner Falcon has shifted to be about one week later over the time period 1979 to 2019. Linear mixed modelling showed the influence of winter conditions and random effects (climate sector of island, year of study) on incubation date in both species. The increase in February rainfall has delayed incubation in the Peregrine Falcon, while we could not identify a specific monthly effect delaying incubation in the Lanner Falcon. In both species, the shift in incubation date has resulted in a decrease in productivity (number of fledglings). Weather conditions in late spring predicted the quality of the breeding site of Lanner Falcons but not of Peregrines. The breeding phenology of both falcons shows a common response to weather conditions on Sicily, however the Lanner Falcon seems more sensitive than the Peregrine to the changing climate. Climate effects add to other anthropogenic impacts negatively affecting the future survival of this insular population, which is the largest in Europe.